UTILIZING GOOGLE SITES TO IMPROVE READING LITERACY IN ELEMENTARY SCHOOLS - Intan Ristanti; Seni Apriliya; Heri Yusuf Muslihin (Jurnal Cakrawala Pendas, 2025)
Reading comprehension is a fundamental skill that is essential for supporting the learning success of elementary school students. However, the implementation of reading instruction in Indonesia still faces various challenges, such as low reading interest, limited access to engaging learning materials, and the dominance of conventional teaching methods. This study aims to examine the role of digital learning media based on Google Site in enhancing elementary school students' reading comprehension skills. This study was conducted using the Systematic Literature Review (SLR) method on scientific articles published between 2015 and 2025. The PRISMA model was applied to ensure transparency and validity in the identification, screening, and inclusion of data. A total of 41 articles met the inclusion criteria and were analyzed using Braun and Clarke’s six-phase thematic analysis. Data extraction was conducted through systematic coding of article content, focusing on the use of Google Sites to support reading instruction. The findings indicate that Google Site facilitates the presentation of multimodal and interactive materials, enhances student motivation and engagement, supports flexible and collaborative learning, and fosters critical and reflective thinking. These characteristics highlight the potential of Google Site as an effective digital learning platform to improve elementary students’ reading skills. This study concludes that Google Site-based learning media has the potential to significantly improve reading comprehension skills if supported by appropriate pedagogical strategies and adequate teacher readiness and infrastructure.